Factors that Influence the Profits of Takaful Companies in Indonesia and Malaysia - Haniatur Rofika; Kurniawati Meylianingrum (Journal of Islamic Economics and Finance Studies, 2024)
Islamic Financial Institutions were established as an application of Muslims' understanding of several principles in Islamic economic law and are developing every year. Takaful contributed 2 percent of total sharia financial assets in 2021; however, in 2019–2020, the development of takaful assets decreased compared to the previous year due to the COVID-19 pandemic. There are several factors that influence profit instability in takaful industry. This study will examine the factors that influence the level of profit in takaful in Indonesia and Malaysia throughout 2017–2022, acquired a sample of 11 firms and obtained secondary data for this study from the official websites of Bank Negara Malaysia (BNM) and the Financial Services Authority (OJK). Utilizing methods for quantitative research, specifically a purposive sampling approach and panel data regression modeling. The research results show that the variables premium, return on investment, risk-based capital, and claims expenses have a major favorable impact on takaful profitability, while liquidity has a major negative impact on the same. Simultaneously, the premium variables, investment returns, risk-based capital, liquidity, and claims costs simultaneously influence the profitability of takaful.